From Face to Screen: Interactive Multimodal Semiotics at Work, by Jyh Wee Sew. - Seok Hoon Quah (Kajian Malaysia, 2018)
Advancements in technology have opened up new resources for communication and the affordances of new media have also been harnessed for the benefit of education. To this end, From Face to Screen: Interactive Multimodal Semiotics at Work is an interesting and credible effort by Sew to illustrate how language and culture interacts in an educational context. Adopting the perspective of multimodal semiotics and a Vygotskyan view of learning as social development, he guides the reader through the semiotic discourse of face-to-face social interaction before focusing his discussion on the Malay language and the educational setting of a university in Singapore. He argues for the "relevance of multimodality in attaining language proficiency with the aid of web-based language literacy as a learning scaffold" (p. 4).